Slides presentation for comparison and evaluation of five different surgically induced astigmatism calculators outcome and analysis reports - Md Mustafa, Md Muziman Syah; Marzuki, Nazaryna; Mohd. Kamal, Khairidzan; Ab. Halim, Noorhazayti (2020)
The slide describe on research findings about comparison of five surgically induced astigmatism calculators outcome and their analysis reports. The presentation was held at 37th American Society of Cataract and Refractive Surgery Annual Meeting in San Diego, United States on May, 3rd 2019.